Pengaruh Cold Pressure Test Pada Tekanan Darah - Dandi Oka Subantara; Elly Nurachmah; Debie Dahlia; Riri Maria (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the difference in blood pressure to the effect of the pressure test. This research method is a systematic review accessed from internet search databases: Scopus, Pro-quest, Willey, Sage Journal, ScienceDirect, and Google Scholar. The study of 9 research articles showed that there were articles that did not have much effect on the Cold Pressure Test (CPT) on blood pressure. All pieces have the same research method, namely Experiment. In conclusion, most studies say that blood pressure affects the stimulation of the sympathetic nerves by performing a Cold Pressure Test (CPT). Keywords: Cold Pressure Test (CPT), Evidence-Based, Cardiovascular